Janus Graphene: Scalable Self‐Assembly and Solution‐Phase Orthogonal Functionalization. Issue 21 (10th April 2019) - Jeon, Intak; Peeks, Martin D.; Savagatrup, Suchol; Zeininger, Lukas; Chang, Sehoon; Thomas, Gawain; Wang, Wei; Swager, Timothy M.
Abstract: Orthogonal functionalization of 2D materials by selective assembly at interfaces provides opportunities to create new materials with transformative properties. Challenges remain in realizing controllable, scalable surface‐selective, and orthogonal functionalization. Herein, dynamic covalent assembly is reported that directs the functionalization of graphene surfaces at liquid–liquid interfaces. This process allows facile addition and segregation of chemical functionalities to impart Janus characteristics to graphenes. Specifically, dynamic covalent functionalization is accomplished via Meisenheimer complexes produced by reactions of primary amines with pendant dinitroaromatics attached to graphenes. Janus graphenes are demonstrated to be powerful surfactants that organize at water/organic, water/fluorocarbon, and organic/fluorocarbon liquid interfaces. This approach provides general access to the creation of diverse surfactant materials and promising building blocks for 2D materials. Abstract : A dynamic covalent assembly is reported that directs graphene functionalization at liquid–liquid interfaces. This process imparts Janus characteristics to the graphene with different chemical functionality on its top and bottom faces. The dynamic covalent functionalization is accomplished via equilibrated Meisenheimer complexes produced by reactions of primary amines with pendant dinitroaromatics attached to the self‐assembled graphenes.